XRF Analysis of Airborne Heavy Metals and Distributions of Environment in Sivas City-Turkey through Dust Samples - Nuhoglu, Yasar; Yazici, Mustafa; Nuhoglu, Cigdem; Kam, Erol; Adar, Elanur; Kuzu, S. Levent; Osmanlioglu, Ahmet E. (Mehmet Sinan Bilgili, 2020)
Sivas, on the Europe-Turkey-Iran highway route, is a city with 329,000 inhabitants located in the central Anatolia and exposed to intense air pollution. In the city center, domestic combustion, medium-scale industry and highways can be contributed to air pollution. In this research, the accumulation of heavy metals (elements) stem from airborne particulate matters was determined on the ground and plant surfaces in Sivas city center. The heavy metals in street dust stem from fossil fuels used in coal and automobiles were analyzed and its environmental risks has been evaluated. Airborne particles were investigated in the city centrum during October 2016. As sources of pollutants, automobile fuels, coal and fuel oil used in domestic combustion were analyzed and their accumulation on objects in the city was examined. Determining the effect of heavy metals given to atmosphere from fuels, street dusts on the main transportation roads and metal concentrations in plant tissues are analyzed by XRF technique and the relationship between them was investigated. The results showed that the main sources of airborne metals are cars and domestic fuels. These results showed the air pollutants present in the city.
Keywords: combustion; airborne heavy metals; street dust; roads; fuels; ELEMENTAL ANALYSIS; RISK-ASSESSMENT; POLLUTION; CONTAMINATION; AREAS; SIZE; XIAN; Engineering; Environmental Sciences & Ecology